CHRONO regulates the circadian clock via the REV-ERBα – BMAL1 loop - Qin Zhou; Lanxin Gao; Ruohan Wang; Shaoying Lan; Dan Li; Ximing Qin (npj Biological Timing and Sleep)
Abstract The period length of the circadian clock is important for organisms to maintain homeostasis. CHRONO has been shown to play an important role in regulating the period of the mammalian clock and has recently been implicated to function in several important physiological aspects. However, the mechanisms underlying transcriptional regulation by CHRONO to determine the circadian period remain elusive. Here, we report that CHRONO acts as a transcriptional repressor on JUN/FOS complexes independent of the classical BMAL1/CLOCK complexes. CHRONO can regulate BMAL1 expression by differentially regulating REV-ERBα and REV-ERBβ. We further developed a mathematical model and the model simulations strongly agreed with our findings that CHRONO acts on both REV-ERB α and BMAL1 to regulate the circadian period. The model also sheds light on the physiological significance of the fact that CHRONO cycles in most of the mammalian tissues. Thus, our experimental and computational approaches reveal the molecular mechanisms of regulating the circadian period by an important circadian component, CHRONO.